Role of vam on growth and phosphorus nutrition of maize with low soluble phosphate fertilization (2010)
The effect of vesicular arbuscular mycorrhizal (VAM) infection on growth and P nutrition in Maize (Zea mays, cv.DDH hybrid) were assessed in Oxisol pot experiment. Maize was grown inoculated with spores of VAM fungi Glomus mosseae or non-inoculated. Low soluble ferrous phosphate (FePO4.4H2O) was added to the mycorrhized and non-micrrohized maized. The dry weight of mycorrhized plants with added phosphate (P) were higher than in mycorrhized plants without added P or non-mycorrhized plants with added P. The amount of P in the soil samples from pots with mycorrhizal plants fertilized with P was evidently smaller than those in samples also fertilized non-mycorrhizal plants. The percentage of P was higher in tissues of fertilized mycorrhial plants than in those mycorrihzed plants without or nonmycorrhized plants with added low-soluble P. These results indicated that plants in VAM symbiosis mobilize P better from low-soluble P than non-mycorrhized plants.